THE EFFECTIVENESS OF USING SILENTWAY METHOD ON STUDENTS’VOCABULARY MASTERY - Evilla Noviana; Sayid Ma’rifatullah (Program Studi Pendidikan Bahasa Inggris, 2024)
The students low motivation in learning English language caused their low in mastering vocabulary. They were not interested because the strategy used by the English teacher when teaching was not interesting. therefore, this research aimed to know the effectiveness of using Silent Way Method on Students’ Vocabulary Mastery. The design of this research was pre-experimental research using one group pre-test and post-test at the seventh grade of MTS Al-Mannan Bagik Nyaka 2023/2024 academic year. The population of this study is class VII at MTS Al-Mannan Bagik Nyaka, in which one class consist of 29 students and this research will just be conducted in one class.The sample of this research is the students of class VII at MTS Al-Mannan, in which the total of them are 29 students. To get the data of this research, the researcher gave test as an instrument which included pre-test and post-test in form of multiple choices test, consist of 20 items questions for each. The learning process was two meetings, As the result, the average in post-test is 79.83 and the pre-test class is 50.86. The researcher employed the paired sample T-test to analyze the data following data calculation. Considering the significance score of 0.000 (<0.005), it can be said that H0 is rejected and H1 is accepted. Therefore, there was a significant effect of using Silent Way Method on Students Vocabulary Mastery.